A agricultura familiar do Seridó potiguar: vulnerabilidade, percepção e adaptação às mudanças climáticas - Andrade, Anna Jéssica Pinto de (2013)
At the semiarid regions of developing countries the rural population has always been vulnerable to the climatic variations e its consequences. The effects of the semiarid climate, together with other biophysics, social and political-economic factors, impair the agricultural production, generating a situation of food insecurity and poverty in the rural areas. With the occurrence of climate change, natural resources of the semiarid regions can became scarcer, what would directly affect the agricultural production and those who depend on it. Therefore, the present study sought to study one of the most susceptible areas to the effects of the semiarid climate and desertification of Rio Grande do Norte, the potiguar s Serido. The study aimed to analyze the socioeconomic and environmental factors that put farmers in a position of vulnerability to the effects of climate; assess their perceptions about climate variations that have already occurred and their knowledge about climate change and global warming, also to identify which adaptation strategies to climate they have adopted at the rural establishment. The survey was conducted in 29 communities of four counties of the potiguar s Serido Caico, Parelhas, Lagoa Nova and Acari. Semi-structured interviews were conducted with local leaders and 241 questionnaires were applied with the family farmers. It was found that in addition to environmental factors such as the scarcity of water resources and climatic conditions, other factors such as the environmental degradation, the small size of the properties, the lack of technical assistance and financial resources and also the low education levels reduce the resilience capacity of family farming to the effects of the Semiarid climate. With the occurrence of climate change, the challenges for family farming at Serido will intensify. If farmers cannot adapt, the impacts may preclude this category of agricultural production causing serious harm to food security and further increasing the vulnerability situation of these populations. Although the farmers perceived changes in climate, the lack resources and information appears as the main reasons preventing the adoption of adaptation strategies. The lack of knowledge about climate change and global warming and the impacts that these phenomena may cause are also limiting factors for adaptation. It is therefore essential to identify the factors that influence the adoption of adaptation strategies, and seek alternatives to living with the semiarid that can strengthen the resilience of family farming and social reproduction that allow agricultural segment, even in a climate change scenario